Math Problem Statement

Find a solution to the following divide-and-conquer recurrence relations. You may use any method.

For all problems, assume that T(1) = 1.

(1) (Home Work) T(n) = 3T(n/2) + n lg n.

T(1) = 1, T(n) = 3T(n/2) + n log n

let n = 2^k, k = 0,1,2,3,...,infinity

T(2^k) = T((2^K)/2) + 2^K (log{2^k})

= T(2^{k-1}) + 2k^2 (k) (log{2})

= T(2^{k-1}) + k2^k

T(2^k) - T(2^{k-1}) = k2^k

(x-1)(x-2) = 0

r_1 = 1, r_2 =2

general solution: T(2^k) = c_1 + A(2^k)

finding constants from boundary conditions

k = 0 => T(2^0) = T(1) = 1

k = 1 => T(2^1) = 3T(1) + 2 (log(2)) = 5

k = 0 => c_1 + A(2^0) = 1

k = 1 => c_1 + A(2^1) = 5

solving for the constants c_1 = -3, A = 4

T(2^k) = -3 + 4(2^k)

since n=2^k => k = log_2{n}

T(n) = -3+4(2^{log_2 n})

is it correct? if not then correct it

Solution

Let's solve the recurrence relation given and verify the solution.

The recurrence relation is: T(n)=3T(n2)+nlognT(n) = 3T\left(\frac{n}{2}\right) + n \log n with the base case T(1)=1T(1) = 1.

Step 1: Let n=2kn = 2^k

Since n=2kn = 2^k, we have k=log2nk = \log_2 n. The recurrence can then be rewritten as: T(2k)=3T(2k1)+2kkT(2^k) = 3T\left(2^{k-1}\right) + 2^k \cdot k where kk replaces logn\log n (since log2n=k\log_2 n = k).

Step 2: Expand the Recurrence

Let's expand the recurrence relation by substituting recursively.

  1. First expansion: T(2k)=3T(2k1)+k2kT(2^k) = 3T(2^{k-1}) + k \cdot 2^k
  2. Second expansion: T(2k1)=3T(2k2)+(k1)2k1T(2^{k-1}) = 3T(2^{k-2}) + (k-1) \cdot 2^{k-1} Substituting this into the first expansion gives: T(2k)=3(3T(2k2)+(k1)2k1)+k2kT(2^k) = 3\left(3T(2^{k-2}) + (k-1) \cdot 2^{k-1}\right) + k \cdot 2^k Simplifying: =32T(2k2)+3(k1)2k+k2k= 3^2 T(2^{k-2}) + 3(k-1) \cdot 2^k + k \cdot 2^k =32T(2k2)+(3(k1)+k)2k= 3^2 T(2^{k-2}) + \left(3(k-1) + k\right) \cdot 2^k
  3. Third expansion: T(2k2)=3T(2k3)+(k2)2k2T(2^{k-2}) = 3T(2^{k-3}) + (k-2) \cdot 2^{k-2} Substituting: T(2k)=33T(2k3)+(32(k2)+3(k1)+k)2kT(2^k) = 3^3 T(2^{k-3}) + \left(3^2(k-2) + 3(k-1) + k\right) \cdot 2^k

Step 3: General Pattern and Sum of Terms

After jj steps, we observe: T(2k)=3jT(2kj)+2ki=0j13i(ki)T(2^k) = 3^j T(2^{k-j}) + 2^k \sum_{i=0}^{j-1} 3^i (k - i) When j=kj = k, we reach the base case T(2kk)=T(1)=1T(2^{k-k}) = T(1) = 1: T(2k)=3kT(1)+2ki=0k13i(ki)T(2^k) = 3^k \cdot T(1) + 2^k \sum_{i=0}^{k-1} 3^i (k - i) Since T(1)=1T(1) = 1, this simplifies to: T(2k)=3k+2ki=0k13i(ki)T(2^k) = 3^k + 2^k \sum_{i=0}^{k-1} 3^i (k - i)

Step 4: Approximate the Summation

The summation i=0k13i(ki)\sum_{i=0}^{k-1} 3^i (k - i) is complex, but it grows asymptotically as O(3k)O(3^k). Therefore: T(n)=O(nlog23)=O(n1.585)T(n) = O(n^{\log_2 3}) = O(n^{1.585})

Final Answer

So, the asymptotic solution to the recurrence relation is: T(n)=Θ(nlog23)Θ(n1.585)T(n) = \Theta(n^{\log_2 3}) \approx \Theta(n^{1.585})

This corrects your initial approach. If you would like further details on the summation step, let me know.


Follow-Up Questions

  1. How can the Master Theorem be applied to verify this solution?
  2. What is the approximate value of log23\log_2 3 and why is it significant?
  3. How would the recurrence change if the term nlognn \log n were replaced with nn?
  4. What does the solution imply about the time complexity in practical scenarios?
  5. Can this recurrence relation be solved by substitution method?

Tip:

When solving recurrence relations, the Master Theorem is a useful shortcut if the recurrence fits its format.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Recurrence Relations
Divide and Conquer
Logarithmic Functions
Asymptotic Analysis

Formulas

T(n) = 3T(n/2) + n log n
T(2^k) = 3^k + 2^k ∑(3^i * (k - i))

Theorems

Master Theorem

Suitable Grade Level

Undergraduate